1994
DOI: 10.3109/00016489409126100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Factors on Cell Proliferation by Human Nasal Septal Chondrocytes Cultured in Monolayer

Abstract: In the field of reconstructive surgery, autologous cartilage grafting is commonly performed to reconstruct skeletal defects. Because of the limited supply of fresh autologous cartilage many investigators concentrate on in vitro production of cartilage tissue. Several growth factors regulate the metabolism and activation of cartilage cells. In order to enhance the culture conditions for cartilage cells, the aim of our investigations was to characterize the influence of transforming growth factor (TGF)-beta, epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
1
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 15 publications
4
14
1
2
Order By: Relevance
“…Although bFGF does not seem to have a known function in the regulation of skeletal growth, it is known to be mitogenic for many cell types [7] including chondrocytes [15]. We recently described the mitogenic effect of bFGF on chondrocyte proliferation [2]. The absence of an effect of bFGF on matrix synthesis of cultured chondrocytes supports prior findings [20,26].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although bFGF does not seem to have a known function in the regulation of skeletal growth, it is known to be mitogenic for many cell types [7] including chondrocytes [15]. We recently described the mitogenic effect of bFGF on chondrocyte proliferation [2]. The absence of an effect of bFGF on matrix synthesis of cultured chondrocytes supports prior findings [20,26].…”
Section: Discussionsupporting
confidence: 73%
“…In a separate publication, we showed that bFGF is able to increase the chondrocyte proliferation in monolayer cultures as the first step of cartilage engineering [2]. We have now demonstrated that TGF-beta is a very suitable candidate for promoting matrix synthesis of chondrocytes cultured in a three-dimensional way.…”
Section: Discussionmentioning
confidence: 87%
“…Our data corroborate with the findings of Bujia et al 5 that the mitogenic actions of growth factors are further enhanced in the presence of FCS. The final cell counts from the growth factor-enhanced 10% FCS medium were Figure 1.…”
Section: Commentsupporting
confidence: 83%
“…Bujia et al 5 tested the impact of epidermal growth factor, transforming growth factor ␤ (TGF-␤), and basic fibroblast growth factor (bFGF) on the cellular proliferation of human septal chondrocytes and found that bFGF was the most potent mitogen of the 3. In 1993, however, Quatela et al 6 reported that although hu- man auricular chondrocyte mitogenesis increased in the presence of bFGF and TGF-␤, septal chondrocytes did not display increased proliferation in the presence of either bFGF or TGF-␤.…”
mentioning
confidence: 99%
“…Growth factors have been used successfully to increase the volume of chondrocytes (Arevalo et al, Paper presented at the Second Bi‐annual Meeting of the Tissue Engineering Society, Orlando, Florida, December 1998). 16–17 …”
Section: Discussionmentioning
confidence: 99%